Risk factors for violence among female forensic inpatients with schizophrenia - Wolf, Viviane; Mayer, Juliane; Steiner, Ivonne; Franke, Irina; Klein, Verena; Streb, Judith; Dudeck, Manuela (Frontiers in Psychiatry, 2023)
Schizophrenia is associated with a heightened risk of violent behavior. However, conclusions on the nature of this relationship remain inconclusive. Equally, the empirical evidence on female patients with schizophrenia spectrum disorders (SSD) is strongly underrepresented. For this purpose, the first aim of the present retrospective follow-up study was to determine the risk factors of violence in a sample of 99 female SSD patients discharged from forensic psychiatric treatment between 2001 and 2017, using three different measures of violence at varying time points (i.e., violent index offense, inpatient violence, and violent recidivism). Potential risk factors were retrieved from the relevant literature on SSD as well as two violence risk assessment instruments (i.e., HCR-20 V3, FAM). Further, we aimed to assess the predictive validity of the HCR-20 V3 in terms of violent recidivism and evaluate the incremental validity of the FAM as a supplementary gender-responsive assessment. The given results indicate strong heterogeneity between the assessed violence groups in terms of risk factors. Particularly, violence during the index offense was related to psychotic symptoms while inpatient violence was associated with affective and behavioral instability as well as violent ideation/intent, psychotic symptoms, and non-responsiveness to treatment. Lastly, violent recidivism was related to non-compliance, cognitive instability, lack of insight, childhood antisocial behavior, and poverty. Further, the application of the HCR-20 V3 resulted in moderate predictive accuracy (AUC = .695), while the supplementary assessment of the FAM did not add any incremental validity. This article provides important insights into the risk factors of violence among female SSD patients while highlighting the importance of differentiating between various forms of violence.